Clean cuisine : an 8-week anti-inflammatory nutrition program that will change the way you age, look, and feel - Larson, Ivy Ingram, 1973- (Berkley Books, 2013)
"There is a diet and exercise plan that covers all the bases--food we should eat and food that tastes good; what is best for our bodies and what is easily doable in the real world--all while offering hunger-free weight loss. Developed by Andy Larson, MD and certified heath fitness specialist Ivy Larson, Clean Cuisine is scientifically proven to reverse diabetes, improve cholesterol and blood pressure, and ease the symptoms of other inflammatory diseases such as multiple sclerosis, fibromyalgia, asthma, allergies, and arthritis. Broken down into eight easy steps and spread over the course of eight weeks, Clean Cuisine will enable readers to transform their bodies one delicious meal at a time by adopting an anti-inflammatory diet and choosing unrefined foods in their most natural, whole state. With guilt-free, delicious recipes and a workout program that has been proven to deliver substantial results with just three thirty-minute sessions a week, Clean Cuisine is the long-term answer to eating for optimal health, disease prevention, weight loss, vitality, longevity, and good taste"--